Combinations of wet corn gluten feed and steam flaked corn in finishing cattle diets - Sindt, J.J.; Montgomery, Sean P.; Farran, T.B.; LaBrune, H.J.; Hunter, R.D.; Higgins, James J.; Ethington, R.T.; Lindquist, R.U.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 152-day experiment was conducted using 615 crossbred steers to evaluate cattle performance when steam-flaked corn in finishing diets was replaced partially with wet corn gluten feed (CGF). Finishing diets contained no wet CGF (0CGF) or 30 and 60% CGF on a dry matter basis (30CGF and 60CGF). Ruminal and fecal pH increased linearly (P<.01) as the proportion of wet corn gluten feed increased. Cattle fed 60CGF gained less than those fed 30CGF (P<.01) and were less efficient than cattle fed 0CGF or 30CGF (P<.05). Dressing percentage was lower (P<.03) for cattle fed 60CGF compared to cattle fed 30CGF. Incidence of liver abscesses increased linearly (P<.01) as the level of CGF increased. Replacing steamflaked corn with wet CGF at 30% of the diet did not alter performance.
Keywords: Beef; Wet corn gluten feed; Steam flaked corn; Finishing cattle